The Economic Burden of Cystoscopy-Based Ureteral Stent Removal in the United States: An Analysis of Nearly 30, 000 Patients. Issue 1 (28th January 2022) - Ghani, Khurshid R.; Rojanasarot, Sirikan; Cutone, Benjamin; Bhattacharyya, Samir K.; Krambeck, Amy E.
Abstract: Introduction: Ureteral stents are commonly placed after ureteroscopy. We examined the rate of cystoscopy-based stent removal (CBSR) following ureteroscopy for stone disease and its economic burden in the United States. Methods: Adults undergoing ureteroscopy and stenting (index surgery) for stone disease between 2014 and 2018 were identified using the IBM® MarketScan® Commercial Database. Patients were categorized as those with CBSR or without CBSR within 6 months post-index surgery. Rate and location of CBSR were assessed. To estimate the economic burden of CBSR, medical costs (2019 U.S. dollars) paid by insurers were calculated at 6 months post-index surgery. A generalized linear model examined the association of CBSR with total costs adjusting for patient characteristics. Results: Among 29, 535 patients meeting the inclusion criteria, 56.5% had CBSR within 6 months. Median time to CBSR was 9 days; 70% of patients with CBSR had their stent removed in the office. Medical costs for CBSR patients were significantly higher than those for nonCBSR patients ($7, 808 vs $6, 231; p <0.0001). The difference was driven by the cost of CBSR ($1, 132 vs $0; p <0.0001) and health care utilization for stone disease ($2, 464 vs $2, 121; p <0.0001). CBSR was associated with a 17% increase in medical costs compared to nonCBSR (OR: 1.17; 95% CI 3.03, 3.46). Conclusions: Over 50% of patients had CBSR within 6 months following ureteroscopy. Medical costs for patients undergoing CBSR were significantly higher and driven by the cost of CBSR and resource utilization for stone disease. Ureteral stents that avoid CBSR can lower medical costs to the health care system.